Optical element material and preparation method thereof
By introducing polymethylene polythiol-polyisocyanate network and rare earth metal complexes into optical materials, the problem of secondary radical cross-linking and chain breaking of optical materials in high-energy irradiation environments is solved, and the high optical uniformity and long-term stability of the materials are achieved.
Patent Information
- Application Number
- CN202510368820.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing optical materials are prone to secondary radical cross-linking or chain breakage in high-energy irradiation environments, resulting in microscopic phase separation, bubble defects and mechanical decay, affecting the accuracy of optical waveguide transmission and holographic imaging.
By introducing a polymethylene polythiol-polyisocyanate network, combining rare earth metal complexes, secondary radical cross-linking and chain breaking in high-energy irradiation environments are reduced, and microscopic phase separation and bubble defects are avoided.
It effectively improves the optical uniformity and long-term stability of the material. After irradiation of γ rays or electron beams at 1MGy level, the refractive index and transmittance attenuation shall not exceed 10%, ensuring the long-term and stable operation of the optical system.
Smart Images

Figure CN119875075A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optical elements, and more specifically, to an optical element material and a preparation method thereof. Background Art
[0002] In the related environmental applications of holographic optical elements, space telescopes, and nuclear industry optical windows, large-aperture optical materials need to maintain high transmittance, low scattering, and ensure the angular stability of holographic imaging in some extreme radiation environments; However, existing epoxy-amine, phenolic or urea-formaldehyde resins are prone to secondary free radical crosslinking or chain scission under the action of high-energy particles and radiation, resulting in microscopic phase separation, bubble defects or mechanical decay, which will affect the accuracy of optical waveguide transmission and holographic imaging; Especially in large-scale holographic components, such as meter-level optical windows, these micro defects are magnified, causing imaging angle drift, enhanced scattering and reduced resolution; in the current market and technology system, there is a lack of specially optimized large-aperture radiation-resistant resin materials, making it difficult to simultaneously meet the optical uniformity, transmittance and long-term stability requirements of holographic imaging. Summary of the invention
[0003] In order to overcome the above-mentioned defects of the prior art, an embodiment of the present invention provides an optical element material and a preparation method thereof. By introducing a polymethylene polythiol-polyisocyanate network and combining it with a rare earth metal complex, the material can effectively reduce secondary free radical crosslinking and chain breakage under high-energy radiation environment, avoid the generation of microscopic phase separation and bubble defects, and solve the problems raised in the above-mentioned background technology.
[0004] To achieve the above object, the present invention provides the following technical solution: an optical element material, comprising the following components: Polymethylene polymercaptan: 40-60 parts, polymethylene polymercaptan including trifunctional or tetrafunctional thiol; Polyisocyanate: 35-50 parts, polyisocyanate includes alicyclic polyisocyanate or hydrogenated aromatic polyisocyanate; Rare earth metal complex: 0.1-1.0 part, the rare earth metal in the rare earth metal complex includes gadolinium Gd, terbium Tb, dysprosium Dy, or a mixture thereof; the complex in the rare earth metal complex includes a complex containing an aromatic heterocycle or a multi-dentate amine carboxylic acid; Dynamic covalent bond precursor or cross-linking aid: 5-15 parts, the dynamic covalent bond precursor or cross-linking aid is used to introduce rearrangeable or self-repairing bonds into the network formed by the polymethylene polythiol and the polyisocyanate; Catalysts and auxiliary agents: 0.05-0.5 parts, the catalysts and auxiliary agents include alkaline catalysts, defoamers and leveling agents for promoting mercapto-isocyanate addition reaction.
[0005] In a preferred embodiment, the trifunctional thiol compound included in the polymethylene polythiol is trimethylolpropane tris(3-mercaptopropionate); The tetrafunctional mercapto compound included in the polymethylene polythiol is pentaerythritol tetrakis (3-mercaptopropionate).
[0006] In a preferred embodiment, the alicyclic polyisocyanate included in the polyisocyanate is isophorone diisocyanate (IPDI) or tetramethyl hexamethylene diisocyanate (TMDI); The hydrogenated aromatic polyisocyanate included in the polyisocyanate is dihydrogenated diphenylmethane diisocyanate (H12MDI) or hydrogenated toluene diisocyanate (H-TDI).
[0007] In a preferred embodiment, the rare earth metal complex comprises a complex containing an aromatic heterocyclic structure or a complex containing a multidentate amine carboxylic acid structure; The complex containing an aromatic heterocyclic structure is selected from gadolinium phthalocyanine (GdPc), terbium benzimidazole (Tb-BI) or dysprosium pyridinecarboxylate (Dy-PCA); The complex containing a multidentate amine carboxylic acid structure is selected from gadolinium diethylenetriaminepentaacetate (Gd-DTPA), terbium ethylenediaminetetraacetate (Tb-EDTA) or dysprosium hydroxyethylidene diphosphonate (Dy-HEDP); In addition, the alkaline catalyst for promoting the mercapto-isocyanate addition reaction is selected from 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), triethylamine (TEA), 1,4-diazabicyclo[2.2.2]octane (DABCO) or a tertiary amine salt catalyst; The defoamer is selected from polysiloxane defoamer, silicone-acrylate copolymer, fluorinated defoamer or polyether modified defoamer; The leveling agent is selected from an organic silicon leveling agent, an acrylic leveling agent, a fluorinated leveling agent or a polyether modified leveling agent.
[0008] In a preferred embodiment, the dynamic covalent bond precursor or cross-linking aid comprises a thiourea bond forming component, a thiol-aldehyde condensation component or a derivative thereof, which is used to form self-repair or rearrangement of the main chain in an irradiation environment.
[0009] In a preferred embodiment, the rare earth metal complex is fully mixed with polymethylene polythiol in an amount of 0.2 to 0.5 parts, and then subjected to addition reaction with polyisocyanate after ultrasonic dispersion to form a uniform solution, so as to evenly distribute the rare earth ion capture centers in the whole material.
[0010] A method for preparing an optical element material comprises the following steps: S1 Precursor mixing: Mix polymethylene polythiol and rare earth metal complex, stir or ultrasonically disperse at 40-60°C, and degas under vacuum; S2 stepwise addition: adding polyisocyanate dropwise to the mixture obtained in S1 under stirring, and then adding a dynamic covalent bond precursor or a crosslinking aid; S3 pre-curing: pre-curing the mixture obtained in S2 at 40-60°C for 2-4 hours, so that the addition reaction between the thiol functional group and the isocyanate functional group mainly occurs, thereby forming a preliminary cross-linking network; S4 post-curing: the pre-cured material is further cured at 80-100°C for 4-8 hours, and the heating temperature is maintained at a gradient control during the process to obtain an optical element material with a complete cross-linking network; S5 stress release treatment: annealing the post-cured material in an environment of 70 to 90° C. for 10 to 24 hours to reduce internal stress and improve optical uniformity.
[0011] In a preferred embodiment, the S4 post-curing process includes at least two heating stages: The first heating stage: from 60℃ to 80℃, the temperature gradient is 2~5℃ / h; The second heating stage: maintain between 80 and 100°C for 4 to 8 hours; This will balance the temperature field inside and outside the material and reduce the generation of microcracks and bubbles.
[0012] In a preferred embodiment, between the S3 pre-curing and the S4 post-curing, a catalyst and an auxiliary agent are added dropwise to regulate the viscosity and curing rate of the system; The final optical element material can have a transmittance of ≥90% in the visible light band (400-700nm), and after irradiation with 1MGy-level gamma rays or electron beams, its refractive index and transmittance attenuation do not exceed 10%.
[0013] Technical effects and advantages of the present invention: By introducing a polymethylene polythiol-polyisocyanate network and combining it with a rare earth metal complex, this material can effectively reduce secondary free radical crosslinking and chain breakage under high-energy irradiation, avoid the generation of microscopic phase separation and bubble defects, and thus relatively improve the optical uniformity of the material; compared with traditional epoxy-amine or phenolic resins, after irradiation with 1MGy-level gamma rays or electron beams, the refractive index and transmittance of this material are attenuated by no more than 10%, ensuring the long-term stable operation of the optical system; Since traditional resins are prone to stress concentration, crack propagation and other problems in large-aperture optical windows or space telescope applications, the present invention introduces dynamic covalent bonds to enable the material to partially self-repair or rearrange its structure after external force or radiation damage, thereby relatively improving the overall mechanical stability; especially in meter-level holographic optical component applications, this feature can reduce the problems of imaging angle drift, scattering enhancement and resolution degradation; The present invention adopts low-absorption, high-transparency alicyclic or hydrogenated aromatic polyisocyanates, such as IPDI and H12MDI, to avoid the optical scattering and yellowing problems caused by traditional aromatic isocyanates, while combining the efficient curing characteristics of the mercapto-isocyanate addition reaction; The material is prepared by using a graded curing strategy of pre-curing, post-curing (80-100°C, 4-8h) and stress release treatment (70-90°C annealing for 10-24h), which can effectively release the curing stress gradient in large-size optical components, reduce warping, microcracks and optical distortion caused by uneven thermal expansion, and improve long-term reliability. By introducing rare earth metal complexes containing aromatic heterocycles or multi-dentate amine carboxylic acid structures into the material, it is beneficial to capture high-energy electrons and reduce the concentration of free radicals, thereby inhibiting the molecular chain degradation and color change of the material in an irradiated environment; compared with traditional resins, the present invention can provide more stable refractive index and mechanical properties, and is suitable for space optics and nuclear industry window applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is an overview diagram of the preparation process of the present invention.
[0015] Figure 2 It is an execution diagram of the preparation process of the present invention.
[0016] Figure 3 The preparation process sequence of the present invention is Figure 1 .
[0017] Figure 4 The preparation process sequence of the present invention is Figure 2 . DETAILED DESCRIPTION
[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Refer to the instruction manual Figure 1-4 , an optical element material in the present invention comprises the following components: Polymethylene polymercaptan: 40-60 parts, polymethylene polymercaptan including trifunctional or tetrafunctional thiol; Polyisocyanate: 35-50 parts, polyisocyanate includes alicyclic polyisocyanate or hydrogenated aromatic polyisocyanate; Rare earth metal complex: 0.1-1.0 part, the rare earth metal in the rare earth metal complex includes gadolinium Gd, terbium Tb, dysprosium Dy, or a mixture thereof; the complex in the rare earth metal complex includes a complex containing an aromatic heterocycle or a multi-dentate amine carboxylic acid; Dynamic covalent bond precursor or cross-linking aid: 5-15 parts, the dynamic covalent bond precursor or cross-linking aid is used to introduce rearrangeable or self-repairing bonds into the network formed by the polymethylene polythiol and the polyisocyanate; Catalysts and auxiliary agents: 0.05-0.5 parts, the catalysts and auxiliary agents include alkaline catalysts, defoamers and leveling agents for promoting mercapto-isocyanate addition reaction.
[0020] In a preferred embodiment, the trifunctional thiol compound included in the polymethylene polythiol is trimethylolpropane tris(3-mercaptopropionate); The tetrafunctional mercapto compound included in the polymethylene polythiol is pentaerythritol tetrakis (3-mercaptopropionate).
[0021] In a preferred embodiment, the alicyclic polyisocyanate included in the polyisocyanate is isophorone diisocyanate (IPDI) or tetramethyl hexamethylene diisocyanate (TMDI); The hydrogenated aromatic polyisocyanate included in the polyisocyanate is dihydrogenated diphenylmethane diisocyanate (H12MDI) or hydrogenated toluene diisocyanate (H-TDI).
[0022] In a preferred embodiment, the rare earth metal complex comprises a complex containing an aromatic heterocyclic structure or a complex containing a multidentate amine carboxylic acid structure; The complex containing an aromatic heterocyclic structure is selected from gadolinium phthalocyanine (GdPc), terbium benzimidazole (Tb-BI) or dysprosium pyridinecarboxylate (Dy-PCA); The complex containing a multidentate amine carboxylic acid structure is selected from gadolinium diethylenetriaminepentaacetate (Gd-DTPA), terbium ethylenediaminetetraacetate (Tb-EDTA) or dysprosium hydroxyethylidene diphosphonate (Dy-HEDP); In addition, the alkaline catalyst for promoting the mercapto-isocyanate addition reaction is selected from 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), triethylamine (TEA), 1,4-diazabicyclo[2.2.2]octane (DABCO) or a tertiary amine salt catalyst; The defoamer is selected from polysiloxane defoamer, silicone-acrylate copolymer, fluorinated defoamer or polyether modified defoamer; The leveling agent is selected from an organic silicon leveling agent, an acrylic leveling agent, a fluorinated leveling agent or a polyether modified leveling agent.
[0023] In a preferred embodiment, the dynamic covalent bond precursor or cross-linking aid comprises a thiourea bond forming component, a thiol-aldehyde condensation component or a derivative thereof, which is used to form self-repair or rearrangement of the main chain in an irradiation environment.
[0024] In a preferred embodiment, the rare earth metal complex is fully mixed with polymethylene polythiol in an amount of 0.2 to 0.5 parts, and then subjected to addition reaction with polyisocyanate after ultrasonic dispersion to form a uniform solution, so as to evenly distribute the rare earth ion capture centers in the whole material.
[0025] A method for preparing an optical element material comprises the following steps: S1 Precursor mixing: Mix polymethylene polythiol and rare earth metal complex, stir or ultrasonically disperse at 40-60°C, and degas under vacuum; S2 stepwise addition: adding polyisocyanate dropwise to the mixture obtained in S1 under stirring, and then adding a dynamic covalent bond precursor or a crosslinking aid; S3 pre-curing: pre-curing the mixture obtained in S2 at 40-60°C for 2-4 hours, so that the addition reaction between the thiol functional group and the isocyanate functional group mainly occurs, thereby forming a preliminary cross-linking network; S4 post-curing: the pre-cured material is further cured at 80-100°C for 4-8 hours, and the heating temperature is maintained at a gradient control during the process to obtain an optical element material with a complete cross-linking network; S5 stress release treatment: annealing the post-cured material in an environment of 70 to 90° C. for 10 to 24 hours to reduce internal stress and improve optical uniformity.
[0026] In a preferred embodiment, the S4 post-curing process includes at least two heating stages: The first heating stage: from 60℃ to 80℃, the temperature gradient is 2~5℃ / h; The second heating stage: maintain between 80 and 100°C for 4 to 8 hours; This will balance the temperature field inside and outside the material and reduce the generation of microcracks and bubbles.
[0027] In a preferred embodiment, between the S3 pre-curing and the S4 post-curing, a catalyst and an auxiliary agent are added dropwise to regulate the viscosity and curing rate of the system; The final optical element material can have a transmittance of ≥90% in the visible light band (400-700nm), and after irradiation with 1MGy-level gamma rays or electron beams, its refractive index and transmittance attenuation do not exceed 10%.
[0028] What needs to be explained about the scheme as a whole is that this scheme is based on optimizing the performance requirements of optical component materials under extreme radiation environments. By selecting specific polymethylene polythiols, polyisocyanates, rare earth metal complexes, dynamic covalent bond precursors or cross-linking aids, catalysts and additives, a high-performance optical material with high visible light transmittance and excellent radiation stability is achieved; The formation process is to firstly mix the polymethylene polythiol containing trifunctional or tetrafunctional thiol groups with the rare earth metal complex containing rare earth metals such as gadolinium, terbium, dysprosium and having a ligand containing an aromatic heterocycle or a multi-dentate amine carboxylic acid structure at 40-60°C, and then ensure uniform dispersion by ultrasonic dispersion and vacuum degassing; Under stirring, alicyclic or hydrogenated aromatic polyisocyanates (such as isophorone diisocyanate, tetramethyl hexamethylene diisocyanate, dihydrogenated diphenylmethane diisocyanate or hydrogenated toluene diisocyanate) and a dynamic covalent bond precursor (such as a thiourea bond or a mercapto-aldehyde condensation component) are added dropwise step by step, and a preliminary cross-linking network is formed by pre-curing at 40 to 60° C. for 2 to 4 hours by utilizing the addition reaction between mercapto groups and isocyanates, that is, the mercapto functional groups and isocyanate functional groups are added to form a polymer network containing urea bonds through a chemical reaction; By curing at 80-100°C for 4-8 hours and using at least two heating stages in the process (the first stage is from 60°C to 80°C, the temperature gradient is 2-5°C / h, and the second stage is kept at 80-100°C for 4-8 hours), the cross-linking network in the whole system is further improved to ensure the balance of the temperature field inside the material, thereby reducing the generation of microcracks or bubbles caused by local temperature differences; After curing, a stress release annealing treatment is performed at 70-90°C for 10-24 hours to further reduce internal stress and improve optical uniformity. This process design makes full use of the rapidity and efficiency of the mercapto-isocyanate addition reaction, avoiding the self-polymerization problem of free radical polymerization in traditional carbon-carbon unsaturated bond polymerization. At the same time, the self-repair and rearrangement of the material network in a high-energy radiation environment are achieved by introducing dynamic covalent bonds. In addition, rare earth metal complexes are pre-mixed with polymethylene polythiol by ultrasonic dispersion under low addition conditions, and then react with polyisocyanate to form uniformly distributed capture centers, which can relatively effectively capture high-energy electrons and free radicals, further enhancing the radiation resistance of the material; Catalysts and additives play a role in controlling the reaction rate and improving the quality of the film, ensuring that the transmittance of the final material in the visible light band (400-700nm) is ≥90%, and that its refractive index and transmittance attenuation does not exceed 10% after 1MGy-level gamma-ray or electron beam irradiation, which makes the material extremely suitable for application scenarios such as holographic optical elements, space telescopes, and nuclear industry optical windows.
[0029] Embodiment 1:
[0030] (1) Formula composition: Polymethylene polymercaptan (tetrafunctional, pentaerythritol tetrakis (3-mercaptopropionate)): 40 parts; Polyisocyanate (isophorone diisocyanate, IPDI): 40 parts; Rare earth metal complex (gadolinium complex, containing multidentate amine carboxylic acid structure): 0.2 parts; Dynamic covalent bond precursor or cross-linking aid (containing thiourea bond forming component): 10 parts; Catalyst and additives (alkaline catalyst DBU + leveling agent, etc.): 0.2 parts; (2) Preparation steps: S1 Precursor mixing: 40 parts of polymethylene polythiol and 0.2 parts of rare earth metal complex were ultrasonically stirred at 50°C for 20 minutes and degassed under vacuum conditions; S2 stepwise addition: under stirring, add 40 parts of IPDI in two drops, and then add 10 parts of dynamic covalent bond precursor or cross-linking aid; S3 pre-curing: pre-curing at 40°C for 3 hours, so that the addition reaction between the thiol functional group and the isocyanate functional group mainly occurs, forming a preliminary cross-linking network; S4 post-curing: heat the pre-cured material to 85-100°C and keep it in this range for 6 hours to further improve the cross-linking network; S5 stress release treatment: annealing in an environment of 80° C. for 10 hours, and then cooling to room temperature to obtain the optical element material of Example 1.
[0031] Embodiment 2:
[0032] (1) Formula composition: Polymethylene polymercaptan (trifunctional, trimethylolpropane tris(3-mercaptopropionate)): 40 parts; Polyisocyanate (tetramethyl hexamethylene diisocyanate, TMDI): 45 parts; Rare earth metal complex (terbium complex, containing aromatic heterocyclic structure): 0.3 parts; Dynamic covalent bond precursor or cross-linking aid (thiol-aldehyde condensation component): 8 parts; Catalyst and additives (alkaline catalyst + defoamer, etc.): 0.2 parts; (2) Preparation steps: S1 Precursor mixing: 40 parts of polymethylene polythiol and 0.3 parts of terbium complex were stirred at 50°C for 30 minutes and vacuum degassed; S2 stepwise addition: 45 parts of TMDI are added dropwise under continuous stirring, and then 8 parts of dynamic covalent bond precursor or crosslinking aid are added; S3 pre-curing: let the mixture stand at 50°C for 2 hours to allow the mercapto groups to partially react with the isocyanate functional groups to form a preliminary network; S4 post-curing: raise the temperature to 80-90°C and maintain for 4 hours, then raise it to 100°C and maintain for 4 hours to fully cure the network; S5 stress release treatment: annealing at 70° C. for 12 hours and then cooling to room temperature to obtain the optical element material of Example 2.
[0033] Embodiment 3:
[0034] (1) Formula composition: Polymethylene polythiol (tetrafunctional): 55 parts; Polyisocyanate (dihydrogenated diphenylmethane diisocyanate, H12MDI): 35 parts; Rare earth metal complex (dysprosium complex, containing multidentate amine carboxylic acid structure): 0.4 parts; Dynamic covalent bond precursor or cross-linking aid: 12 parts; Catalyst and additives (alkaline catalyst + other additives): 0.3 parts; (2) Preparation steps: S1 Precursor mixing: 55 parts of polymethylene polythiol and 0.4 parts of dysprosium complex were stirred at 40°C for 20 minutes and degassed under vacuum; S2 stepwise addition: slowly dropwise add 35 parts of H12MDI and add 12 parts of dynamic covalent bond precursor or crosslinking aid in batches; S3 pre-curing: pre-curing at 45°C for 3 hours to form a preliminary cross-linking network; S4 post-curing: heating at 85°C and then rising to 100°C, maintaining for 6 hours; S5 stress release treatment: the cured sample is annealed at 80° C. for 24 hours and then cooled to room temperature to obtain the optical element material of Example 3.
[0035] Embodiment 4:
[0036] (1) Formula composition: Polymethylene polythiol (trifunctional): 50 parts; Polyisocyanate (hydrogenated toluene diisocyanate, H-TDI): 40 parts; Rare earth metal complex (gadolinium complex, containing aromatic heterocyclic structure): 0.5 parts; Dynamic covalent bond precursor or cross-linking aid: 5 parts; Catalysts and additives (alkaline catalyst + leveling agent, etc.): 0.05 parts; (2) Preparation steps: S1 Precursor mixing: 50 parts of trifunctional polymethylene polythiol and 0.5 parts of gadolinium complex were ultrasonically stirred at 55°C for 15 minutes and degassed; S2 stepwise addition: 40 parts of H-TDI are added stepwise, and 5 parts of dynamic covalent bond precursor or crosslinking aid are added; S3 pre-curing: pre-curing at 40°C for 4 hours to complete the main addition reaction; S4 post-curing: maintain at 80-90°C for 8 hours to form a complete cross-linking network; S5 stress release treatment: annealing at 70° C. for 10 hours and then cooling to room temperature to obtain the optical element material of Example 4.
[0037] Embodiment 5:
[0038] (1) Formula composition: Polymethylene polythiol (tetrafunctional group): 45 parts; Polyisocyanate (IPDI): 40 parts; Rare earth metal complex (terbium benzimidazole complex): 0.2 parts; Dynamic covalent bond precursor or cross-linking aid (containing thiourea bond forming component): 15 parts; Catalyst and additives (alkaline catalyst + leveling agent, etc.): 0.3 parts; (2) Preparation steps: S1 Precursor mixing: 45 parts of tetrafunctional polymethylene polythiol and 0.2 parts of terbium benzimidazole complex were stirred at 60°C for 30 minutes and degassed; S2 stepwise addition: 40 parts of IPDI were added dropwise twice, and 15 parts of dynamic covalent bond precursor or cross-linking aid were gradually added; S3 pre-curing: pre-curing for 3 hours at 50°C to obtain a preliminary cross-linked network; S4 post-curing: maintain at 90°C for 6 hours; S5 stress release treatment: annealing at 80° C. for 12 hours and then cooling to room temperature to obtain the optical element material of Example 5.
[0039] Embodiment 6:
[0040] (1) Formula composition: Polymethylene polythiol (trifunctional): 60 parts; Polyisocyanate (TMDI): 35 parts; Rare earth metal complex (Gd-DTPA): 0.3 parts; Dynamic covalent bond precursor or cross-linking aid: 10 parts; Catalyst and additives (alkaline catalyst + other additives): 0.2 parts; (2) Preparation steps: S1 Precursor mixing: Stir 60 parts of trifunctional polymethylene polythiol and 0.3 parts of Gd-DTPA complex at 50-60°C for 20 minutes and degas under vacuum; S2 stepwise addition: 35 parts of TMDI are added dropwise, and 10 parts of dynamic covalent bond precursor or crosslinking aid are added; S3 pre-curing: stand at 40°C for 2 hours to form a preliminary network; S4 post-curing: maintain at 85-95°C for 5 hours; S5 stress release treatment: annealing at 75°C for 10 hours and then cooling to room temperature to obtain the optical element material of Example 6.
[0041] Embodiment 7:
[0042] (1) Formula composition: Polymethylene polythiol (tetrafunctional): 42 parts; Polyisocyanate (H12MDI): 45 parts; Rare earth metal complex (Dy-HEDP): 0.4 parts; Dynamic covalent bond precursor or cross-linking aid: 10 parts; Catalyst and additives (alkaline catalyst + defoamer, etc.): 0.1 part; (2) Preparation steps: S1 Precursor mixing: 42 parts of tetrafunctional thiol and 0.4 parts of Dy-HEDP were ultrasonically stirred at 45°C for 20 minutes and vacuum degassed; S2 stepwise addition: 45 parts of H12MDI are added dropwise, and then 10 parts of dynamic covalent bond precursor or crosslinking aid are added; S3 pre-curing: pre-curing at 50°C for 2.5 hours to initially form a network; S4 post-curing: heat to 90°C and maintain for 7 hours; S5 stress release treatment: annealing at 75°C for 12 hours and then cooling to room temperature to obtain the optical element material of Example 7.
[0043] Embodiment 8:
[0044] (1) Formula composition: Polymethylene polymercaptan (trifunctional): 58 parts; Polyisocyanate (H-TDI): 35 parts; Rare earth metal complex (gadolinium phthalocyanine complex): 0.3 parts; Dynamic covalent bond precursor or cross-linking aid: 12 parts; Catalyst and additives (alkaline catalyst + leveling agent, etc.): 0.3 parts; (2) Preparation steps: S1 Precursor mixing: 58 parts of trifunctional polymethylene polythiol and 0.3 parts of gadolinium phthalocyanine complex were stirred at 60°C for 30 minutes and degassed; S2 stepwise addition: 35 parts of H-TDI are added dropwise, and 12 parts of dynamic covalent bond precursor or crosslinking aid are added in batches; S3 pre-curing: pre-curing for 3 hours at 40°C; S4 post-curing: maintain at 90°C for 6 hours to obtain a complete cross-linked network; S5 stress release treatment: After annealing at 80°C for 10 hours, the material of Example 8 was obtained.
[0045] Embodiment 9:
[0046] (1) Formula composition: Polymethylene polythiol (tetrafunctional group): 50 parts; Polyisocyanate (IPDI): 35 parts; Rare earth metal complex (Dy-PCA): 0.5 parts; Dynamic covalent bond precursor or cross-linking aid: 10 parts; Catalyst and additives (alkaline catalyst + other additives): 0.3 parts; (2) Preparation steps: S1 Precursor mixing: 50 parts of tetrafunctional polymethylene polythiol and 0.5 parts of Dy-PCA were stirred at 50°C for 20 minutes and degassed; S2 stepwise addition: 35 parts of IPDI are added stepwise, followed by 10 parts of dynamic covalent bond precursor or crosslinking aid; S3 pre-curing: maintain at 45°C for 3 hours to form a preliminary network; S4 post-curing: keep at 85℃ for 8 hours to fully cure the network; S5 stress release treatment: annealing at 70° C. for 24 hours and then cooling to room temperature to obtain the optical element material of Example 9.
[0047] Embodiment 10: (1) Formula composition: Polymethylene polythiol (trifunctional): 42 parts; Polyisocyanate (TMDI): 40 parts; Rare earth metal complex (Tb-BI): 0.2 parts; Dynamic covalent bond precursor or cross-linking aid: 12 parts; Catalyst and additives (alkaline catalyst + defoamer, etc.): 0.2 parts; (2) Preparation steps: S1 Precursor mixing: 42 parts of trifunctional polymethylene polythiol and 0.2 parts of Tb-BI were stirred at 50°C for 20 minutes and degassed under vacuum; S2 stepwise addition: 40 parts of TMDI are added dropwise, and then 12 parts of dynamic covalent bond precursor or crosslinking aid are dispersedly added; S3 pre-curing: pre-curing for 2 hours at 40°C to form a preliminary network; S4 post-curing: raise the temperature to 90°C and maintain for 7 hours; S5 stress release treatment: annealing at 80°C for 12 hours and then cooling to room temperature to obtain the optical element material of Example 10.
[0048] Embodiment 11: (1) Formula composition: Polymethylene polythiol (tetrafunctional): 46 parts; Polyisocyanate (H12MDI): 35 parts; Rare earth metal complex (Dy-HEDP): 0.3 parts; Dynamic covalent bond precursor or cross-linking aid: 6 parts; Catalyst and additives (alkaline catalyst + leveling agent, etc.): 0.2 parts; (2) Preparation steps: S1 Precursor mixing: 46 parts of tetrafunctional polymethylene polythiol and 0.3 parts of Dy-HEDP were stirred at 40°C for 25 minutes and vacuum degassed; S2 stepwise addition: slowly dropwise add 35 parts of H12MDI and add 6 parts of dynamic covalent bond precursor or crosslinking aid; S3 pre-curing: pre-curing at 45°C for 2.5 hours; S4 post-curing: maintain at 85°C for 5 hours; S5 stress release treatment: annealing at 70°C for 10 hours and then cooling to room temperature to obtain the optical element material of Example 11.
[0049] Embodiment 12: (1) Formula composition: Polymethylene polymercaptan (trifunctional): 58 parts; Polyisocyanate (H-TDI): 40 parts; Rare earth metal complex (Tb-EDTA): 0.2 parts; Dynamic covalent bond precursor or cross-linking aid: 12 parts; Catalyst and additives (alkaline catalyst + leveling agent, etc.): 0.3 parts; (2) Preparation steps: S1 Precursor mixing: 58 parts of trifunctional polymethylene polythiol and 0.2 parts of Tb-EDTA were stirred at 60°C for 15 minutes and degassed; S2 stepwise addition: 40 parts of H-TDI are added dropwise, and 12 parts of dynamic covalent bond precursor or crosslinking aid are added in sequence; S3 pre-curing: pre-curing for 3 hours at 40°C to form a preliminary network; S4 post-curing: raise the temperature to 90°C and maintain for 6 hours; S5 stress release treatment: annealing at 80°C for 12 hours and then cooling to room temperature to obtain the optical element material of Example 12.
[0050] Embodiment 13: (1) Formula composition: Polymethylene polythiol (tetrafunctional): 52 parts; Polyisocyanate (IPDI): 40 parts; Rare earth metal complex (dysprosium complex, containing multidentate amine carboxylic acid structure): 0.3 parts; Dynamic covalent bond precursor or cross-linking aid: 10 parts; Catalyst and additives (alkaline catalyst + defoamer, etc.): 0.3 parts; (2) Preparation steps: S1 Precursor mixing: 52 parts of tetrafunctional polymethylene polythiol and 0.3 parts of rare earth metal complex were stirred at 50°C for 25 minutes and degassed under vacuum; S2 stepwise addition: 40 parts of IPDI are added dropwise, and 10 parts of dynamic covalent bond precursor or cross-linking aid are added in batches; S3 pre-curing: pre-curing at 45°C for 2 hours; S4 post-curing: maintained at 90°C for 6 hours to form a higher cross-linking network; S5 stress release treatment: annealing at 70°C for 10 hours and then cooling to room temperature to obtain the optical element material of Example 13.
[0051] Embodiment 14: (1) Formula composition: Polymethylene polythiol (trifunctional): 46 parts; Polyisocyanate (TMDI): 35 parts; Rare earth metal complex (terbium complex, containing aromatic heterocyclic structure): 0.4 parts; Dynamic covalent bond precursor or cross-linking aid: 10 parts; Catalyst and additives (alkaline catalyst + leveling agent, etc.): 0.2 parts; (2) Preparation steps: S1 Precursor mixing: 46 parts of trifunctional polymethylene polythiol and 0.4 parts of rare earth metal complex were ultrasonically stirred at 50°C for 20 minutes and degassed; S2 stepwise addition: 35 parts of TMDI are added dropwise, and 10 parts of dynamic covalent bond precursor or crosslinking aid are added; S3 pre-curing: pre-curing at 40°C for 2.5 hours; S4 post-curing: the temperature rises to 85-90°C and maintains for 5 hours; S5 stress release treatment: annealing at 80°C for 10 hours and then cooling to room temperature to obtain the optical element material of Example 14.
[0052] Embodiment 15: (1) Formula composition: Polymethylene polythiol (tetrafunctional group): 60 parts; Polyisocyanate (H12MDI): 35 parts; Rare earth metal complex (gadolinium complex, containing multidentate amine carboxylic acid structure): 0.2 parts; Dynamic covalent bond precursor or cross-linking aid: 8 parts; Catalyst and additives (alkaline catalyst + defoamer, etc.): 0.2 parts; (2) Preparation steps: S1 Precursor mixing: 60 parts of tetrafunctional polymethylene polythiol and 0.2 parts of rare earth metal complex were stirred at 50°C for 20 minutes and degassed; S2 stepwise addition: slowly dropwise add 35 parts of H12MDI and simultaneously add 8 parts of dynamic covalent bond precursor or crosslinking aid; S3 pre-curing: pre-curing at 40℃ for 2 hours; S4 post-curing: maintain at 90°C for 7 hours to fully cure the network; S5 stress release treatment: annealing at 75°C for 12 hours and then cooling to room temperature to obtain the optical element material of Example 15.
[0053] Embodiment 16: (1) Formula composition: Polymethylene polythiol (trifunctional): 45 parts; Polyisocyanate (H-TDI): 40 parts; Rare earth metal complex (Tb-BI): 0.5 parts; Dynamic covalent bond precursor or cross-linking aid: 6 parts; Catalyst and additives (alkaline catalyst + leveling agent, etc.): 0.2 parts; (2) Preparation steps: S1 Precursor mixing: 45 parts of trifunctional polymethylene polythiol and 0.5 parts of Tb-BI were stirred at 55°C for 20 minutes and degassed; S2 stepwise addition: 40 parts of H-TDI are added dropwise, followed by 6 parts of dynamic covalent bond precursor or crosslinking aid at one time; S3 pre-curing: pre-curing for 3 hours at 40°C to form a preliminary network; S4 post-curing: raise the temperature to 90°C and maintain for 6 hours to fully cross-link the network; S5 stress release treatment: annealing at 70°C for 10 hours and then cooling to room temperature to obtain the optical element material of Example 16.
[0054] Visible light transmittance experimental comparison table based on Examples 1-16:
[0055] Based on the refractive index experimental comparison table in Examples 1-16 with a 25°C environment and sodium D line as the test light source:
[0056] Based on the experimental comparison table measured by differential scanning calorimetry DSC in Examples 1-16:
[0057] Experimental comparison table of tensile strength retention rate after γ irradiation based on Examples 1-16 (retention rate compared with the initial tensile strength value after treatment in a 1MGy γ ray environment):
[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An optical element material, characterized in that: It consists of the following components: Polymethylene polymercaptan: 40-60 parts, polymethylene polymercaptan including trifunctional or tetrafunctional thiol; Polyisocyanate: 35-50 parts, polyisocyanate includes alicyclic polyisocyanate or hydrogenated aromatic polyisocyanate; Rare earth metal complex: 0.1-1.0 part, the rare earth metal in the rare earth metal complex includes gadolinium Gd, terbium Tb, dysprosium Dy, or a mixture thereof; the complex in the rare earth metal complex includes a complex containing an aromatic heterocycle or a multi-dentate amine carboxylic acid; Dynamic covalent bond precursor or cross-linking aid: 5-15 parts, the dynamic covalent bond precursor or cross-linking aid is used to introduce rearrangeable or self-repairing bonds into the network formed by the polymethylene polythiol and the polyisocyanate; Catalysts and auxiliary agents: 0.05-0.5 parts, the catalysts and auxiliary agents include alkaline catalysts, defoamers and leveling agents for promoting mercapto-isocyanate addition reaction.
2. An optical element material according to claim 1, characterized in that: The trifunctional thiol compound included in the polymethylene polythiol is trimethylolpropane tris (3-mercaptopropionate); The tetrafunctional mercapto compound included in the polymethylene polythiol is pentaerythritol tetrakis (3-mercaptopropionate).
3. An optical element material according to claim 2, characterized in that: The alicyclic polyisocyanate included in the polyisocyanate is isophorone diisocyanate or tetramethyl hexamethylene diisocyanate; The hydrogenated aromatic polyisocyanate included in the polyisocyanate is dihydrogenated diphenylmethane diisocyanate or hydrogenated toluene diisocyanate.
4. An optical element material according to claim 3, characterized in that: The rare earth metal complex includes a complex containing an aromatic heterocyclic structure or a complex containing a multidentate amine carboxylic acid structure; The complex containing an aromatic heterocyclic structure is selected from gadolinium phthalocyanine, terbium benzimidazole or dysprosium pyridine carboxylate; The complex containing a multidentate amine carboxylic acid structure is selected from gadolinium diethylenetriaminepentaacetate, terbium ethylenediaminetetraacetate or dysprosium hydroxyethylidene diphosphonate.
5. An optical element material according to claim 4, characterized in that: The dynamic covalent bond precursor or cross-linking auxiliary agent comprises a thiourea bond forming component, a thiol-aldehyde condensation component or a derivative thereof, and is used for forming self-repair or rearrangement of the main chain in an irradiation environment.
6. An optical element material according to claim 5, characterized in that: The rare earth metal complex is fully mixed with polymethylene polythiol in an amount of 0.2 to 0.5 parts, and then subjected to addition reaction with polyisocyanate after ultrasonic dispersion to form a uniform solution, so as to evenly distribute the rare earth ion capture centers in the whole material.
7. A method for preparing an optical element material, characterized in that: The following steps are involved: S1 Precursor mixing: Mix polymethylene polythiol and rare earth metal complex, stir or ultrasonically disperse at 40-60°C, and degas under vacuum; S2 stepwise addition: adding polyisocyanate dropwise to the mixture obtained in S1 under stirring, and then adding a dynamic covalent bond precursor or a crosslinking aid; S3 pre-curing: pre-curing the mixture obtained in S2 at 40-60°C for 2-4 hours, so that the addition reaction between the thiol functional group and the isocyanate functional group mainly occurs, thereby forming a preliminary cross-linking network; S4 post-curing: the pre-cured material is further cured at 80-100°C for 4-8 hours, and the heating temperature is maintained at a gradient control during the process to obtain an optical element material with a complete cross-linking network; S5 stress release treatment: anneal the post-cured material in an environment of 70 to 90°C for 10 to 24 hours.
8. The method for preparing an optical element material according to claim 7, characterized in that: The S4 post-curing process includes at least two heating stages: The first heating stage: from 60℃ to 80℃, the temperature gradient is 2~5℃ / h; The second heating stage: maintain between 80 and 100°C for 4 to 8 hours; This will balance the temperature field inside and outside the material and reduce the generation of cracks and bubbles.
9. The method for preparing an optical element material according to claim 8, characterized in that: Between the S3 pre-curing and the S4 post-curing, a catalyst and an auxiliary agent are added dropwise to adjust the viscosity and curing rate of the system.
Citation Information
Patent Citations
High-transmittance and blue light-proof eye protection eyeglass and production method thereof
CN108164627A
Photochromic optical article and method of manufacturing same
CN111954832A
Plastic spectacle lens
JP2013061653A
Polymer particles and use thereof
US20150152322A1
Self-healing polythiourethane polymerizable composition, self-healing polythiourethane produced therefrom, and self-healing optical material produced using same
WO2024085454A1